A cross-sectional observational study of quality of life in adult short bowel syndrome patients: what role does autologous gut reconstruction play? - Braun, Julia; Arensmeyer, Jan Christian; Hausen, Annekristin; Stolz, Verena; Keller, Peter Sebastian; Amarell, Nicola; Lurje, Georg; Schäfer, Nico; Kalff, Jörg C.; von Websky, Martin W. (Nutrition in clinical practice, 2025)
Background Intestinal failure (IF) describes a condition of insufficient absorption capacity and general function of the gastrointestinal tract and may necessitate long-term intravenous fluid and nutrient supplementation. Quality of life (QoL) may be reduced in these patients. The aim of the study was to analyze QoL by two tools (SBS-QoL and SF-12) to elucidate which parameters impact QoL in patients with IF. Methods QoL was assessed in a cohort of 105 patients with IF at a tertiary referral center for intestinal rehabilitation. Complete data for SBS-QoL and SF-12 were available in 44 of 81 surviving patients at a single time point for a cross-sectional analysis. Medical data, outcome parameters, and comorbidities (Charlson comorbidity index [CCI]) were extracted and entered in a prospective database for analysis and correlation with QoL assessment. Results Subscales of SBS-QoL and SF-12 highly correlated with each other (P = −0.64 for physical subscales; P = −0.75 for mental subscales). Significant differences in QoL were detected in patients with Messing Type I (end-jejunostomy) and Type III anatomy (ileocolonic anastomosis) (one-way ANOVA: P < 0.05). Performance of autologous gut reconstruction (AGR) was associated with significantly better physical QoL. CCI correlated significantly with QoL scores. Longer duration of illness resulted in higher QoL in SBS-QoL (reduction of 0.15 per month; P = 0.045). Conclusion Both SBS-QoL and SF-12 are useful to determine QoL in patients with IF. AGR was associated with improved QoL by changing SBS-related anatomy and function. Thus, AGR surgery should be included in the treatment plan whenever possible. Comorbidities should be addressed interdisciplinarily to improve QoL.